Detection of Melamine Based on the Fluorescence Changes of Nitrogen-Doped Carbon Dots - Yin, Wenzhi; Ma, Chaoqun; Zhu, Tuo; Gu, Jiao; Zhu, Chun; Li, Lei; Chen, Guoqing (Journal of Spectroscopy, 2021)
In order to determine the concentration of melamine, nitrogen-doped carbon dots (NCDs) were synthesized in one step as a fluorescent probe. Uric acid and diethylenetriamine were used as carbon source and nitrogen source, respectively. The experimental results showed that the fluorescence of NCDs can be quenched by mercury ions (Hg2+). Due to the strong coordination affinity between the carbon-nitrogen heterocyclic of melamine and Hg2+, part of Hg2+ coordinated with melamine when melamine was mixed with Hg2+. Then, the fluorescence of the added NCDs was quenched by the remaining Hg2+. Therefore, the concentration of melamine could be determined. The results show that the method has high sensitivity in wide measuring range that the linear ranges are 50–400 μg/L and 800–2500 μg/L, and the R2 is 0.997 and 0.988, respectively, with the limit of detection (LOD) of 21.76 μg/L. The NCDs are easy to fabricate, and the detection method is easy to implement. In this study, a new method for melamine detection was established, and the proposed method for melamine detection can provide some insights for food safety detection.